Improving Perinatal Care in the Rural Regions Worldwide by Wireless Enabled Antepartum Fetal Monitoring: A Demonstration Project. (26th January 2015) - Tapia-Conyer, Roberto; Lyford, Shelley; Saucedo, Rodrigo; Casale, Michael; Gallardo, Hector; Becerra, Karen; Mack, Jonathan; Mujica, Ricardo; Estrada, Daniel; Sanchez, Antonio; Sabido, Ramon; Meier, Carlos; et al.
Abstract : Background . Fetal and neonatal morbidity and mortality are significant problems in developing countries; remote maternal-fetal monitoring offers promise in addressing this challenge. The Gary and Mary West Health Institute and the Instituto Carlos Slim de la Salud conducted a demonstration project of wirelessly enabled antepartum maternal-fetal monitoring in the state of Yucatán, Mexico, to assess whether there were any fundamental barriers preventing deployment and use. Methods . Following informed consent, high-risk pregnant women at 27–29 weeks of gestation at the Chemax primary clinic participated in remote maternal-fetal monitoring. Study participants were randomized to receive either prototype wireless monitoring or standard-of-care. Feasibility was evaluated by assessing technical aspects of performance, adherence to monitoring appointments, and response to recommendations. Results . Data were collected from 153 high-risk pregnant indigenous Mayan women receiving either remote monitoring (n = 74 ) or usual standard-of-care (n = 79 ). Remote monitoring resulted in markedly increased adherence (94.3% versus 45.1%). Health outcomes were not statistically different in the two groups. Conclusions . Remote maternal-fetal monitoring is feasible in resource-constrained environments and can improve maternal compliance for monitoring sessions. Improvement in maternal-fetal health outcomes requires integration of such technology into sociocultural context and addressing logistical challenges of access to appropriate emergency services.